Keterlibatan Orang Tua dalam Pendidikan di Jepang - Hanifa Zahara; Mislaini Mislaini; Hayatul Mardhiyah (BADAN PENERBIT STIEPARI PRESS, 2025)
Each nation has a different education system in each country, according to the cultural values ​​of the region. To see the character of a nation, it is necessary to see how children's education is based on the cultural values ​​it adheres to. And Japan is known as a nation with discipline, hard work, and independence that is educated from an early age. The nature of the Japanese people becomes like that because it is formed through the way parents in Japan educate their children in the family environment. This study aims to reveal the system or way parents in Japan educate their children. The length of this study is important when considering the fact that Japan has now become a developed country and has strong economic stability and security. The role of character that shapes the mental attitude of the Japanese people is an important factor. The position and function of the family in the character education of the Japanese people as the leading sector. Parents as role models for their children and parents are the first madrasah for their children, in introducing and instilling the values ​​of empathy, discipline, ethics.